The effect of E-Service Quality, E-Trust, Price and Brand Image Towards E-Satisfaction and Its Impact on E-Loyalty of Traveloka's Customer - Wilis, Ratih Anggoro; Nurwulandari, Andini (2020)
This study aims to analyze the effect of E-Service Quality, E-Trust, Price, Brand Image to the E-Satisfaction, and E-Loyalty of Online Travel Agent Traveloka. This research method uses a quantitative approach with a survey method with Structural Equation Modeling (SEM) analysis techniques from the AMOS Version 22 statistical software package. Variable measurements were carried out using questionnaires using Likert model scoring. The sampling technique used is the Non-Probability Sampling method, the saturated sample technique (Census) totaling 182 respondents or equal to the population. The results of the analysis show that each variable (E-Service Quality, E-Trust, Price, Brand Image) has a positive and real effect to the E-Satisfaction and E-Loyalty to Online Travel Agent Traveloka with Critical Ratio (CR)> 1.96 (Critical value for degrees 95% confidence), probability value (p) <0.05 and regression coefficient value> 0.00 (Positive). Based on the results of the study concluded that E-Service Quality, E-Trust, Price, and Brand Image have a positive effect on E-Satisfaction and also on E-Loyalty. Traveloka site provided the best E-Service Quality; Traveloka also provides a high-security system to promote the Traveloka site. Traveloka's website runs a competitive price strategy by offering attractive promos to its customers; besides that, Traveloka also collaborates with banks to provide attractive promo offers. Traveloka's Brand Image has represented the overall perception of the brand and was formed from the information and experience of the brand.